Allocation of Interline Power Flow Controller-Based Congestion Management in Deregulated Power System - Muhammad Safdar Sial; Qinghua Fu; Talles Vianna Brugni (Advances in Engineering and Intelligence Systems)
The present paper provides an optimal location of the Interline Power Flow Controller (IPFC) method in the power system using the Sperm Whales Swarm Optimization (SWSO) algorithm. The main aim of the IPFC’s optimal location is to achieve an appropriate structure for congestion management in restructured power systems. The IPFC model changes the power flow by injecting power into the system. One of the most important issues in reducing power losses and improving the voltage profile, which leads to a reduction in generation and congestion costs, is determining the appropriate location for installing IPFC. Therefore, an objective function is defined, including the stated parameter, minimizing the generation cost, congestion costs, power losses, and improving the voltage profile. Using the upgraded SWSO algorithm, a new approach to the optimal location of IPFC is presented. For validation, the proposed method has been implemented on the IEEE 14 bus restructured power system. By examining the obtained results, the performance of the proposed algorithm is better than the Genetic Algorithm (GA) and Particle Swarm Optimization (PSO) algorithms. It causes a further reduction in the generation cost, congestion costs, and power losses and improves the voltage profile. Therefore, it is suggested that the proposed method be applied to the actual world restructured power system.